6G Networks – A Technological Foundation for Autonomous Systems and the Internet of Everything - Dvoinikova, I.; Sotnik, S. (NURE, 2026)
The study examines the evolutionary transition from 5G networks to 6G technologies, marking a paradigm shift from the IoT to the IoE. Four key components of the 6G architecture were analyzed: the implementation of native artificial intelligence, ensuring ultra-low latency (0,1-1 ms) to enable the «Tactile Internet», the use of Integrated Sensing and Communication technology, and support for ultra-massive connectivity (100 million devices/km²). The significance of these features for the operation of fully autonomous robotic systems and the scaling of smart environments was substantiated. The study concludes on the role of 6G as critical infrastructure for human-machine cooperation in the context of Industry 4.0 and 5.0. У роботі досліджено еволюційний перехід від мереж 5G до технологій 6G, що знаменує зміну парадигми від «Інтернету речей» (IoT) до «Інтернету всього» (IoE). Проаналізовано чотири ключові компоненти архітектури 6G: впровадження нативного штучного інтелекту, забезпечення наднизьких затримок (0,1-1 мс) для реалізації «Тактильного Інтернету», використання технології інтегрованої сенсорики й комунікації (ISAC) та підтримка ультра-масових підключень (100 млн пристроїв/км²). Обґрунтовано значення цих характеристик для функціонування повністю автономних робототехнічних систем та масштабування розумних середовищ. Зроблено висновок про роль 6G як критичної інфраструктури для кооперації людей і машин в умовах Індустрії 4.0 та 5.0.
Мережі 6G – технологічний фундамент для автономних систем та інтернету всього
Keywords: 6G networks; IoE; native artificial intelligence; integrated sensors; мережі 6G; IoE; нативний штучний інтелект; інтегрована сенсорика